2021
DOI: 10.1155/2021/4482201
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Self-Adhesive Soft Silicone Common Foam Dressing in Reducing Intraoperative Pressure Ulcers in Elderly ICU Patients

Abstract: Pressure ulcer (PU), also called pressure injury, is localized damage to the skin and underlying soft tissues, usually over bony prominences, as a result of sustained mechanical loads applied to the tissues. However, in many situations, complete off-loading of sacral PUs is not possible. Minimising the exposure of wounds and their surroundings to elevated mechanical loads is crucial for healing. We for the first time reported the application of Meipicang in the prevention and treatment of intraoperative pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…Para isso, esses profissionais devem realizar boas práticas, que consistem em um conjunto de técnicas e procedimentos, no manejo com esses pacientes que visem garantir cuidados com a pele do mesmo, redução da sobrecarga tissular e estimular e auxiliar na mudança de decúbito, para que assim seja reduzida a possibilidade da ocorrência desse evento adverso (Wang et al, 2021). Assim, o objetivo central do estudo foi analisar na literatura cientifica quais os cuidados de enfermagem para prevenção de lesão por pressão em pacientes em Unidade de Terapia Intensiva.…”
Section: Introductionunclassified
“…Para isso, esses profissionais devem realizar boas práticas, que consistem em um conjunto de técnicas e procedimentos, no manejo com esses pacientes que visem garantir cuidados com a pele do mesmo, redução da sobrecarga tissular e estimular e auxiliar na mudança de decúbito, para que assim seja reduzida a possibilidade da ocorrência desse evento adverso (Wang et al, 2021). Assim, o objetivo central do estudo foi analisar na literatura cientifica quais os cuidados de enfermagem para prevenção de lesão por pressão em pacientes em Unidade de Terapia Intensiva.…”
Section: Introductionunclassified
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%